Separation, preconcentration, and spectrophotometry in inorganic analysis - Marczenko, Zygmunt (Analytical spectroscopy library, 2000)
Spectrophotometry enables one to determine, with good precision and sensitivity, almost all the elements present in small and trace quantities of any material. The method is particularly useful in the determination of non-metals and allows the determination elements in a large range of concentrations (from single % to low ppm levels) in various materials. In Separation, Preconcentration and Spectrophotometry in Inorganic Analysis, much attention has been paid to separation and preconcentration methods, since they play an essential role in increasing the selectivity and sensitivity of spectrophotometric methods. Separation and preconcentration methods have also been utilised in other determination techniques. Spectrophotometric methods which are widely used for the determination of the elements in a large variety of inorganic materials are presented in the book whilst separation and preconcentration procedures combined with spectrophotometry are also described. This book contains recent advances in spectrophotometry, detailed discussion of the instrumentation, and the techniques and reagents used for spectrophotometric determination of elements in a wide range of materials as well as a detailed discussion of separation and preconcentration procedures that precede the spectrophotometric detection.